Fiberized Diamond-Based Vector Magnetometers - Chatzidrosos, Georgios; Rebeirro, Joseph Shaji; Zheng, Huijie; Omar, Muhib; Brenneis, Andreas; Stürner, Felix M.; Fuchs, Tino; Buck, Thomas; Rölver, Robert; Schneemann, Tim; Blümler, Peter; Budker, Dmitry; et al. (Frontiers in Photonics, 2021)
We present two fiberized vector magnetic-field sensors, based on nitrogen-vacancy (NV) centersin diamond. The sensors feature sub-nT/√Hz magnetic sensitivity. We use commercially availablecomponents to construct sensors with a small sensor size, high photon collection, and minimalsensor-sample distance. Both sensors are located at the end of optical fibres with the sensor-headfreely accessible and robust under movement. These features make them ideal for mapping magneticfields with high sensitivity and spatial resolution ( ≤ mm). As a demonstration we use one of thesensors to map the vector magnetic field inside the bore of a ≥ 100 mT Halbach array. The vectorfield sensing protocol translates microwave spectroscopy data addressing all diamonds axes andincluding double quantum transitions to a 3D magnetic field vector.